Effects of Solvents on the Amount of Anthraquinone - Nurul Ain, Jumri; Mimi Sakinah, A. M.; Zularisam, A. W. (Universiti Malaysia Pahang, 2016)
Dyes derived from natural sources have appeared as a significant alternative to synthetic dyes. Recently, the scientific community has begun to show interest in Morinda citrifolia as it is one of the natural sources. The roots of these plants were reported to be a good source of important compounds, known as anthraquinones, which have been proved an important naturally occurring pigments that are widely distributed in nature to produce yellow or red dyes. However, it is not known which method and types of solvent will obtain the highest anthraquinone extract from Morinda citrifolia. In order to tackle this problem, this research was carried out to study effects of solvents on the concentration of anthraquinone using solvent extraction method at room temperature for 10 hour. Ethanol, acetone and acetonitrile were types of solvent used. The anthraquinone extract was analyzed using UV-Vis Spectrophotometer afterwards. It was observed that the acetone is the best solvent to extract the highest anthraquinone concentration followed by ethanol and acetonitrile respectively. Acetone gave anthraquinone concentration about 0.0844g/L, while ethanol and acetonitrile was 0.0440g/L and 0.0355g/L correspondingly. It also shows that acetone gave the best color in which brick red color. The results suggested that the solvent extraction method able to yield colorants from Morinda citrifolia which can work out commercially, but the color varies based on the types of solvent used.